Seed Quality Management (SQM) at the CGIAR Genebanks - Hay, Fiona; Gouda, Arnaud; Ndjiondjop, Marie-Noelle; Baum, Katherine, J.; Santos, Luis Guillermo; Jawad, Rama; Yazbek, Mariana; Oyatomi, Olaniyi; Salvador, Olorunnisola Funmilola; Olbana, Tamiru (2025)
The 11 genebanks of the CGIAR together maintain hundreds of thousands of accessions of the most important global crops, but also of minor crops, trees and forages. As part of the CGIAR Genebanks Initiative, the Seed Quality Management community of practice has been carrying out various research activities to improve the efficiency and effectiveness of genebank operations, some of which is summarized here.